The Development of the MonoTalk (Monopoly Talk) Game for Group Guidance Services to Enhance Interpersonal Communication - Ida Nur Qomariyah; Muwakhidah (PSDKU Guidance and Counseling, Universitas Negeri Surabaya, 2026)
This research aims to develop MonoTalk (Monopoly Bicara) as a group guidance tool to improve interpersonal communication among junior high school students. This study employed a Research and Development (R&D) method, adopting the Borg and Gall model, which initially consisted of ten stages. However, this study was limited to five stages: needs analysis, planning, product development, expert validation, and user testing. Data analysis techniques included an inter-rater agreement model and descriptive analysis. The results of expert validation and user testing showed an agreement index of 1.00 for the usability, accuracy, and feasibility aspects, reflecting a very high level of validity. Descriptive statistical analysis showed that content experts rated the product with average scores of 3.76 (usability), 3.91 (accuracy), and 3.92 (feasibility). Media experts gave average scores of 3.90 (visual design), 3.97 (introduction), and 4.00 (game media). Furthermore, user testing with school counselors yielded an average score of 4.00 for all aspects, indicating excellent acceptance. Student responses indicated that 75% rated the product as very useful, 97% as very accurate, and 94% as very appropriate. Based on the results of this study, it can be concluded that the MonoTalk game is very useful, very appropriate, and very suitable for use as a supporting medium for group guidance services to foster interpersonal communication among junior high school students. Future research is recommended to investigate the effectiveness of the MonoTalk game and its implementation in broader educational settings involving larger and more diverse participant groups.